2017
DOI: 10.18632/oncotarget.17102
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of individual patient data on the impact of the BIM deletion polymorphism on treatment outcomes in epidermal growth factor receptor mutant lung cancer

Abstract: BackgroundA germline deletion in the BIM (BCL2L11) gene has been shown to impair the apoptotic response to tyrosine kinase inhibitors (TKIs) in vitro but its association with poor outcomes in TKI-treated non-small cell lung cancer (NSCLC) patients remains unclear. We conducted a systematic review and meta-analysis on both aggregate and individual patient data to address this issue.ResultsIn an aggregate data meta-analysis (n = 1429), the BIM deletion was associated with inferior PFS (HR = 1.51, 95%CI = 1.06–2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 54 publications
3
8
0
Order By: Relevance
“…The NCC Oncopanel test also detected an Asian‐specific polymorphism in BCL2L11/BIM , which is thought to be associated with resistance of lung cancer to epidermal growth factor receptor tyrosine kinase inhibitors . The deletion allele conferring resistance was observed in 24 (12.8%) cases, which is consistent with the percentage in the Asian population …”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The NCC Oncopanel test also detected an Asian‐specific polymorphism in BCL2L11/BIM , which is thought to be associated with resistance of lung cancer to epidermal growth factor receptor tyrosine kinase inhibitors . The deletion allele conferring resistance was observed in 24 (12.8%) cases, which is consistent with the percentage in the Asian population …”
Section: Resultssupporting
confidence: 63%
“…27 The deletion allele conferring resistance was observed in 24 (12.8%) cases, which is consistent with the percentage in the Asian population. 28 According to evidence levels 1A-3A, 109 cases (58.2%) harbored at least 1 actionable gene aberration (Figure 2A) Next, we examined the percentage of cases with each tumor type ( Figure 2B). When the 187 cases were categorized as carcinoma…”
Section: Percentage Of Cases Harboring Actionable Gene Aberrationsmentioning
confidence: 99%
“…While the presence of the BIM deletion reduces the first-line response to imatinib in CML patients [ 19 ], in EGFR-NSCLC patients it predicts an inferior OS compared to individuals without the deletion (28.8 vs 40.2 months respectively, p<0.017) [ 20 ]. Four independent groups from Taiwan, China, and Japan have replicated our findings [ 21 25 ], although two South Korean centres did not show any differences [ 26 , 27 ], which may possibly be due to genetic differences between East Asians [ 28 , 29 ].…”
Section: Introductionsupporting
confidence: 68%
“…Others have previously demonstrated that BIM expression is required for response to EGFR TKIs (35, 3739). Additionally, BIM polymorphisms which result in decreased expression of functional BIM protein, are associated with resistance to EGFR TKIs (32, 54, 55). Here, we establish that TWIST1 suppresses BIM expression through direct binding at both the promoter and intronic regions.…”
Section: Discussionmentioning
confidence: 99%